PTU-044 Tertiary Centre Experience Of 360 Degree Side-viewing Video Capsule Endoscopy. (9th June 2014) - Goel, R; Borrow, DM; Patel, KV; Nasr, I; Ward, M; Ray, S; Irving, PM; Sanderson, JD; Anderson, SH
Abstract : Introduction: Since it's development in 1999, video capsule endoscopy (VCE) has become the investigation of choice for examining the small bowel. Recently, a novel panoramic 360 degree side-viewing VCE (Capsovision, Medical Innovations, USA) was launched. It differs from previous capsules in that no data recorder or sensors are required. The images are stored on the capsule itself, which when passed, must be retrieved and sent to the endoscopy reader for analysis. We report our initial experience of this novel VCE. Methods: We retrospectively analysed the first 51 side-viewing VCE over a 6-month period at our institution. All patients had a clear liquid diet as preparation the day before. Results: 51 patients (26 males) underwent examination with the side-viewing VCE. 39 (76.4%) examinations were completed and 12 were incomplete. This included 4 which were lost due to being flushed away. Over the same time period, forward-viewing VCE complete results were available in 83.2% patients. 1 of the incomplete examinations was due to a NSAID-induced stricture, subsequently diagnosed with a forward-viewing VCE. 31 patients had good bowel preparation, 11 satisfactory preparation and 6 were reported as having poor bowel preparation. The duodenal ampulla was reliably identified in 3/47 (6.4%) examinations. Pathology was identified in 11/47 (23.4%) examinations. Conclusion: Side-viewing VCE was well tolerated and completed examination results were available for 76.4% of patients examined. Our findings did not correlate with previous reported results (71%) regarding the identification rate of the duodenal papilla as a small bowel landmark with side-viewing VCE. Advantages of the side-viewing VCE are not needing the patient to wear a recorder, with the data being stored in the capsule itself. This enables multiple patients to be examined on the same day and the number of examinations is not limited by available data recorders. Patients can also take the capsule home and take the capsule at any time which can be useful in the investigation of obscure GI bleeding. Side-viewing VCE is comparable to forward viewing VCE with respect to cost and accuracy. Disclosure of Interest: None Declared.